2017
DOI: 10.1111/psyp.12962
|View full text |Cite
|
Sign up to set email alerts
|

Salient‐but‐irrelevant stimuli cause attentional capture in difficult, but attentional suppression in easy visual search

Abstract: Search for a shape target is difficult when its shape is similar to the shape of the surrounding nontargets and easy when it is dissimilar. We asked whether interference from a salient but irrelevant color singleton depended on search difficulty as manipulated by target-nontarget similarity. We found that interference was strong in difficult searches, and the occurrence of an electrophysiological index of attentional selectivity (the N2pc component) confirmed that attention was captured by the distractor. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 46 publications
8
47
0
Order By: Relevance
“…This is a consistent finding with the previous study showing that the capture effect by a salient singleton distractor increased as search efficiency decreased (Barras and Kerzel, 2017b). Further, these results are relevant to recent findings by Barras and Kerzel (2017a). They showed that there was attentional capture by the color distractor in inefficient search, whereas there was suppression to the distractor in efficient search.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is a consistent finding with the previous study showing that the capture effect by a salient singleton distractor increased as search efficiency decreased (Barras and Kerzel, 2017b). Further, these results are relevant to recent findings by Barras and Kerzel (2017a). They showed that there was attentional capture by the color distractor in inefficient search, whereas there was suppression to the distractor in efficient search.…”
Section: Resultssupporting
confidence: 92%
“…The modulation of attentional capture by search efficiency is also supported by recent neuroscienfic evidence (Barras and Kerzel, 2017a). In the difficult visual search of this study, an N2pc component of the event-related potential (ERP) occurred to the color singleton distractor.…”
supporting
confidence: 55%
“…Further, the color of the nontargets (and distractor, if applicable) changed randomly from trial to trial between green and red to increase interference effects compared to constant colors . In a related EEG-study, we used the same stimuli and confirmed that the saliency of the color singleton did not vary between high and low shapebased similarity (Barras & Kerzel, 2017). In that study, we asked observers to respond to the color singleton and varied the similarity between an irrelevant shape singleton (i.e., the square) and the nontarget shapes (i.e., circles vs. diamonds).…”
Section: Methodsmentioning
confidence: 81%
“…Recent studies have indicated that the P D component is a neurophysiological marker of an active suppression mechanism (Barras & Kerzel, , ; Hickey et al., ; Sawaki et al., ). Notably, this positive component has been given various names in previous studies.…”
Section: Discussionmentioning
confidence: 99%